EVALUASI KESESUAIAN LAHAN TANAMAN SERBA GUNA ATAU MULTI PURPOUSE TREE SPECIES (MPTS) DI DESA MANDALAWANGI KECAMATAN NAGREG KABUPATEN BANDUNG - Rian Susila (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
Nagreg District, Bandung Regency is part of the upstream Citarum Watershed (DAS) which is the main watershed in West Java. Mandalawangi Village is one of the upstream watershed areas is identical to the steep topography so that the risk of surface runoff is higher, so must planted with annual plants that can be used by the community on land like this, MPTS plants. The object of research is to analyze the land suitability of MPTS plant species in the research location. This study uses data on biophysical characteristics, namely land height, soil type and rainfall. Based on these parameters, the research location is divided into 4 land unit maps. Field observations found 6 types of multipurpose plants, namely Nangka (Artocarpus heterophyllus), Kopi Arabika (Coffea arabica), Mangga (Mangifera indica), Nangka (Artocarpus heterophylus), Jengkol (Archidendron pauciflorum) and Petai (Parkia speciosa). The results of the analysis of land suitability evaluation at LMU 1 plants that match the characteristics of the land include Nangka (Artocarpus heterophyllus), Mangga (Mangifera indica) and Kopi Arabika (Coffea arabica). In LMU 2 there are four suitable species, namely Nangka (Artocarpus heterophyllus), Mangga (Mangifera indica), Jengkol (Archidendron pauciflorum) and Petai (Parkia speciosa). Whereas at LMU 3 and 4 only one species is suitable respectively, Sukun (Artocarpus altilis) and Kopi Arabika (Coffea arabica).